2022
DOI: 10.1161/strokeaha.122.039584
|View full text |Cite
|
Sign up to set email alerts
|

Direct, Indirect, and Combined Extracranial-to-Intracranial Bypass for Adult Moyamoya Disease: An Updated Systematic Review and Meta-Analysis

Abstract: BACKGROUND: Moyamoya disease is a chronic, progressive cerebrovascular disease involving occlusion or stenosis of the terminal portion of the internal carotid artery. We conducted an updated systematic review and meta-analysis to investigate clinical and angiographic outcomes comparing direct, combined, and indirect bypass for the treatment of moyamoya disease in adults. METHODS: Two independent authors performed Preferred Reporting Items for Systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 39 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…But it's important to note that this study also had a high rate of bypass occlusion (10%). Another meta-analysis noted that although both direct bypass and combined bypass were superior to indirect bypass in the treatment of early stroke, late stroke and late intracerebral hemorrhage, indirect bypass was significantly superior to both direct and combined bypass in the treatment of early intracerebral hemorrhage ( 23 ). Sam et al ( 24 ) evaluated the improvement of cerebral blood flow in MMD and steno-occlusive disease patients before and after cerebrovascular revascularization by blood-oxygen-level-dependent cerebrovascular reactivity MRI and computerized prospective targeting of CO 2 , and they found that unilateral revascularization not only reversed gray matter thinning and cognitive loss in the affected hemisphere but also significantly improved in the unaffected hemisphere, however, this study included both direct and indirect bypass surgery, so it cannot be directly stated which surgery method is more effective.…”
Section: Discussionmentioning
confidence: 99%
“…But it's important to note that this study also had a high rate of bypass occlusion (10%). Another meta-analysis noted that although both direct bypass and combined bypass were superior to indirect bypass in the treatment of early stroke, late stroke and late intracerebral hemorrhage, indirect bypass was significantly superior to both direct and combined bypass in the treatment of early intracerebral hemorrhage ( 23 ). Sam et al ( 24 ) evaluated the improvement of cerebral blood flow in MMD and steno-occlusive disease patients before and after cerebrovascular revascularization by blood-oxygen-level-dependent cerebrovascular reactivity MRI and computerized prospective targeting of CO 2 , and they found that unilateral revascularization not only reversed gray matter thinning and cognitive loss in the affected hemisphere but also significantly improved in the unaffected hemisphere, however, this study included both direct and indirect bypass surgery, so it cannot be directly stated which surgery method is more effective.…”
Section: Discussionmentioning
confidence: 99%
“…90,91 There is a lack of randomized data regarding revascularization strategy in ischemic moyamoya. Most metaanalyses 70,73,74,[92][93][94] and their source studies have several limitations, including nonrandomized allocation of treatment, heterogeneity in age and clinical presentation of cohorts, unblinded outcome assessment, variable length of follow-up, and redundancy in the included cohorts. Although some data may suggest that the direct bypass or combined approach has advantages over the indirect approach for stroke prevention 73,74,[92][93][94] and angiographic outcomes, 70,73,92,93 without differences in perioperative complications, 70,73,74 such studies have major limitations, and no strong conclusions can be made.…”
Section: Surgical Treatment Surgical Interventionsmentioning
confidence: 99%
“…In a recent meta-analysis comparing the three bypass techniques in adults, Nguyen et al [69] found that DB/CB conferred benefits in terms of late stroke recurrence versus IB, with no dissimilarities in terms of perioperative outcomes. Notably, while cerebral hyperperfusion is an undesirable complication of DB in adult patients, this phenomenon is much less frequently observed in pediatric patients and so the conclusions of this study should not constitute a reason to avoid DB in children.…”
Section: In Comparison With the Literaturementioning
confidence: 99%